2017
DOI: 10.1088/1757-899x/170/1/012024
|View full text |Cite
|
Sign up to set email alerts
|

Hydrometallurgical Treatment for Mixed Waste Battery Material

Abstract: Abstract.Hydrometallurgical experiments are generally required to assess the appropriate treatment process before the establishment of the industrial recovery process for waste battery materials. The effects of acid systems and oxidants in metal leaching were studied. The comprehensive leaching effects of the citric acid were superior to the sulfuric acid. The potassium permanganate inhibits the dissolution of metals. Thermodynamic calculations showed that metals precipitate more easily in sulfuric acid system… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…For example, the precipitation of Co (IV) oxide from a synthetic cobalt-citrate complex in alkaline conditions using sodium lauryl sulfate (SDS) and in a protracted procedure is possible [21]. Solven extraction to achieve a selective separation of nickel, cobalt, and manganese from the citrate leach solution as suggested by the literature should be investigated for the MHP citrate system [22][23][24][25]. It is postulated that the inefficiency in achieving selective leaching is due to the possibility that the metal and citrate ions create a strong bond in the solution; hence, the selective separation of Co and Mn is challenging.…”
Section: Effect Of Oxidants On Metal Dissolutionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the precipitation of Co (IV) oxide from a synthetic cobalt-citrate complex in alkaline conditions using sodium lauryl sulfate (SDS) and in a protracted procedure is possible [21]. Solven extraction to achieve a selective separation of nickel, cobalt, and manganese from the citrate leach solution as suggested by the literature should be investigated for the MHP citrate system [22][23][24][25]. It is postulated that the inefficiency in achieving selective leaching is due to the possibility that the metal and citrate ions create a strong bond in the solution; hence, the selective separation of Co and Mn is challenging.…”
Section: Effect Of Oxidants On Metal Dissolutionmentioning
confidence: 99%
“…For example, the precipitation of Co (IV) oxide from a synthetic cobalt-citrate complex in alkaline conditions using sodium lauryl sulfate (SDS) and in a protracted procedure is possible [21]. Solven extraction to achieve a selective separation of nickel, cobalt, and manganese from the citrate leach solution as suggested by the literature should be investigated for the MHP citrate system [22][23][24][25].…”
Section: Effect Of Oxidants On Metal Dissolutionmentioning
confidence: 99%
“…Citric acid is an excellent acid for selective metal dissolution compared to sulfuric acid. Ma et al observed from the experiment they conducted on spent LIBs that the citric acid with reducing agent H 2 O 2 shows a significant Co and Ni metal leaching process but slows dissolution of other metals such as Mn, Fe, and Zn. Musariri et al studied a 1–1.5 M citric acid solution for the leaching process to recover lithium, cobalt, and nickel from LIBs.…”
Section: Recycling Process Of Li-ion Batteriesmentioning
confidence: 99%